Now you see it - Perry, Carol J. (Perry, Carol J. Witch City mystery, 2023)
"Just married, Lee and her husband, Detective Sergeant Pete Mondello, are settling into their new home when Lee is dubbed WICH-TV's new 'Historical Documentary Chief Executive.' Her first subject is the brand-new Salem International Museum, slated to be a location for traveling blockbuster exhibits, starting with 'Seafaring New England.' From research to collecting artifacts of Salem's long-ago days as a shipping capital, the project is a challenge--but when the driver of a truckload of antiquities turns up dead under a pile of fall leaves, it's not quite the kind of challenge Lee expected... Soon, Lee and Pete are dredging up clues along with a hardy crew of helpers, including Lee's librarian aunt, Ibby, Lee's best friend and practicing witch, River North--and of course the clairvoyant cat, O'Ryan. But when a ship model in the exhibit's collection appears to be haunted, Lee will have to dive into her own treasure trove of psychic gifts before a killer comes to the surface to strike again..."--